Treaty-Making Power In Federal States With Special Reference To The Malaysian Position - Khin, Abdul Ghafur Maung Sein (Journal of Malaysian and Comparative Law, 2019)
Since States possess international personality, they undoubtedly have the power to conclude international treaties, agreements or conventions. Nevertheless, in the context of the federal States, the issue of which organ has the capacity to make treaties or whether the component units of the federation can enter into treaties with other countries still remains a hotly debated and controversial question. The present article attempts to answer the question on the basis of international law rules and constitutional law principles. Special references is made to the treaty-making capacity of Malaysia, which is also a federal State, in the light of the Federal Constituion, case law and the treaty-making practice. This article is written on the proposition that in Malaysia, treaty-making power is vested in the Federal Government (i.e. Yang di-Pertuan Agong) and that the executive authorities of the component States have no power whatsoever to conclude treaties with foreign countries.